PENINGKATAN APRESIASI DONGENG SISWA KELAS VII-1 SMP NEGERI I SUMENEP MELALUI PEMBELAJARAN KONTEKSTUAL - RUSLIY . (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2009)
AbstractContextual approach derived from the context of learner is one of approaches which can be used to give good opportunity for the students to improve not only their reading interest through lerning folktale but also their appreciation toward folktale. Stories or folktale given to the students should be stories or folktale which tell about students life and environment. In this research, the folktales teken on studied are folktaleswhich have cultural background in Madura, specially in Sumenep.